Data from: "Transcriptome sequencing of the Antarctic Colobanthus quitensis (Kunth) Bartl (Caryophillaceae)" in Genomic Resources Notes Accepted 1 February 2015 – 31 March 2015 - Bertini, Laura; Proietti, Silvia; Caruso, Carla (Zenodo, 2015)
This article documents the public availability of raw transcriptome sequence data and assembled contigs of the Antarctic plant Colobanthus quitensis grown in two different climatic conditions. BLAST hits are also provided. SRX814890 Sequence files of Colobanthus quitensis transcriptome grown in two different climatic conditions. Sequences were obtained using Illumina Platform Hi-Seq2000. Assembly: Paired-end reads were put through the sequencing pipeline consisting of base calling using Illumina Pipeline, trimming for quality with ERNE and from adapters with Cutadapt software. High quality reads from all libraries combined were then assembled into contigs using the de novo assembler toolbox of CLC Genomics Workbench version 6.5.1 setting default parameters but 'word size' to 64. Blast Hits of Colobanthus quitensis transcriptome All contigs were screened against Viridiplantae protein databases Nr using BLASTx (e-value<10-5) (Altschul et al. 1990). blastx_C_quietensis_vs_Viridiplantae_no_Ptrichocarpa_no_Vvinifera.csv